2021
DOI: 10.1038/s41598-021-83632-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of Trichophyton rubrum and Microsporum canis during keratin degradation

Abstract: Keratin is important and needed for the growth of dermatophytes in the host tissue. In turn, the ability to invade keratinised tissues is defined as a pivotal virulence attribute of this group of medically important fungi. The host–dermatophyte interaction is accompanied by an adaptation of fungal metabolism that allows them to adhere to the host tissue as well as utilize the available nutrients necessary for their survival and growth. Dermatophyte infections pose a significant epidemiological and clinical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
(35 reference statements)
0
12
0
4
Order By: Relevance
“…A recent report evaluated the primary metabolites obtained from T. rubrum and M. canis under growth in glucose and keratin sources [ 59 ]. This study highlighted the presence of cysteine, alanine, kynurenic acid, and riboflavin during keratin growth, and oxaloacetate, uracil, hydroxyproline, pyridoxine, and glutathione when glucose was used as a nutrient.…”
Section: Virulence Attributes Of Dermatophytesmentioning
confidence: 99%
“…A recent report evaluated the primary metabolites obtained from T. rubrum and M. canis under growth in glucose and keratin sources [ 59 ]. This study highlighted the presence of cysteine, alanine, kynurenic acid, and riboflavin during keratin growth, and oxaloacetate, uracil, hydroxyproline, pyridoxine, and glutathione when glucose was used as a nutrient.…”
Section: Virulence Attributes Of Dermatophytesmentioning
confidence: 99%
“…These scenarios are mainly justified by the common contact of children with household pets, such as cats and dogs, 52 and the common asymptomatic carriage of this fungus in children, making them a reservoir of infection. Another potential explanation is the wide keratinolytic enzymatic profile of M. canis 65 . A cross‐sectional Palestinian study conducted between 2012 and 2013 revealed that M. canis was the sole species isolated from clinically diagnosed patients with Tinea capitis 66 .…”
Section: Species Distribution and Antifungal Resistance Among Dermato...mentioning
confidence: 99%
“…These organisms have the capacity to breakdown keratin, such as feathers, hairs, nails, horns, and claws 14 – 16 . Dermatophytes have been divided into three ecological groups: geophilic and zoophilic (i.e., Trichophyton verrucosum , Microsporum canis ), which can spread the infection to humans, and anthropophilic dermatophytes such as T. rubrum and T. interdigitale, causing dermatophytosis in humans 17 19 . The Chrysosporium group comprises over 60 species (i.e., A. keratinophilus , A. fulvescens , Ch.…”
Section: Introductionmentioning
confidence: 99%